PSYCHOLOGICAL TERMINOLOGY IN THE SYSTEM OF MODERN ENGLISH (Conferencea, 2023)
The rapid development of science and technology, modern information technologies, significant changes in the life of our society, namely the openness of borders, the intensification of the processes of intercultural communication dictates the need for a comprehensive description, study and analysis of new layers of terminological vocabulary. Today, terminology plays a leading role in people's communication in the world, being a source of information, a tool for mastering a specialty and a kind of driving force of scientific and technological progress.